ADNAN MENDERES - RECEP TAYYİP ERDOĞAN: "THE POLITICAL HEIR" OF THE "POLITICAL MARTYR" (Journal of Oriental Studies, 2023)
This article examines the indirect political relationship between Adnan Menderes and Recep Tayyip Erdogan, two major political personalities in Turkish republican history. Due to his reforms that were meant to change the Kemalist political course in Turkey in the 1950s and his execution following the 1960 military coup, Menderes, who served as Prime Minister during that time, is sometimes regarded as a "political martyr" by a broad community of right-wing voters. Erdogan, the current president, is positioned as Menderes' "political heir '' by drawing on historical background and ideological parallels. Erdogan routinely makes reference to Menderes' legacy in his political discourse while promoting similar populist ideas and supporting religious conservatism in opposition to secularist movements. Parallels also exist with regard to criticisms of both leadersi dictatorial inclinations and polarizing political discourse. By analysing this relationship, the topic provides a lens into understanding how narratives of past political figures can be repurposed in contemporary politics, thus enriching the discourse on political continuity and change in Turkey.
Keywords: Adnan Menderes; Recep Tayyip Erdogan; Political Islam; Political Legacy; 2023 Presidential elections in Turkey